Analisis Pengaruh Green Accounting, Sales Growth, dan Good Corporate Governance Terhadap Kinerja Keuangan Perusahaan Energi yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2021-2023 - Andi Almaira Ardiansyah; Adam Zakaria; Hera Khairunnisa (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to provide empirical evidence on the influence of green accounting, sales growth, and good corporate governance on the financial performance of energy companies in Indonesia. Financial performance is measured using Return on Equity (ROE). The study employs a quantitative method using secondary data sources obtained from companies annual reports and sustainability reports. The population of this study consists of energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. A total of 120 observation sample were selected using purposive sampling and analyzed using panel data regression analysis with EViews 13 software. The results show that sales growth has a positive and significant effect on financial performance, while green accounting and good corporate governance do not have a significant effect on financial performance.